2018
DOI: 10.1136/bjsports-2017-098769
|View full text |Cite
|
Sign up to set email alerts
|

Quadriceps tendon autograft for arthroscopic knee ligament reconstruction: use it now, use it often

Abstract: Traditional bone-patellar tendon-bone and hamstring tendon ACL grafts are not without limitations. A growing body of anatomic, biomechanical and clinical data has demonstrated the utility of quadriceps tendon autograft in arthroscopic knee ligament reconstruction. The quadriceps tendon autograft provides a robust volume of tissue that can be reliably harvested, mitigating the likelihood of variably sized grafts and obviating the necessity of allograft augmentation. Modern, minimally invasive harvest techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
72
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 46 publications
3
72
0
5
Order By: Relevance
“…There has been increased interest in the quadriceps tendon (QT) as an alternative autologous graft source for ACLR 13. The QT graft has a long track record in ACL revision and posterior cruciate ligament (PCL) reconstruction surgery.…”
Section: Objectivesmentioning
confidence: 99%
“…There has been increased interest in the quadriceps tendon (QT) as an alternative autologous graft source for ACLR 13. The QT graft has a long track record in ACL revision and posterior cruciate ligament (PCL) reconstruction surgery.…”
Section: Objectivesmentioning
confidence: 99%
“…5,37,44 The QT provides a thicker graft with favorable tensile properties—namely, a higher load to failure, higher strain at failure, and higher Young modulus of elasticity as compared with BPTB and HT autografts. 10,11,41,43 Furthermore, it may be harvested with or without a femoral bone block. 5 Retrospective and prospective cohort studies have revealed comparable patient-reported outcomes with all 3 grafts.…”
mentioning
confidence: 99%
“…5 Retrospective and prospective cohort studies have revealed comparable patient-reported outcomes with all 3 grafts. 3,10,18,23,28,41,42 Proponents of the QT autograft appreciate that the function of the HT may be preserved, since hamstring muscles act as agonists of the ACL and dynamic medial stabilizers of the knee. 12,13,27 While graft rupture rates of the QT autograft (2.0%-4.8%) are comparable with those of BPTB autografts, 7,9,10,28,31,32,34 little is known about the rates of graft rupture between QT and HT autografts in primary ACL surgery.…”
mentioning
confidence: 99%
“…The quadriceps tendon is a novel graft choice for ACL reconstruction in adolescent and adult patients. 6,21,22,32-34 The quadriceps tendon, either as an isolated soft tissue graft or with a patellar bone block, has been shown to provide favorable outcomes among adult and adolescent patients. 21,23,32 The quadriceps tendon graft is associated with decreased incidence of postoperative anterior knee pain and better extensor strength recovery as compared with the bone–patellar tendon–bone graft.…”
mentioning
confidence: 99%